DISTRIBUSI SPASIAL INDUSTRI DI KABUPATEN PADANG PARIAMAN - Sendi Sendi (Horizon, 2021)
This study aims to obtain data, manage, analyze, discuss the spatial distribution of industries in Padang Pariaman District, seen from: 1) Spatial Distribution of Large and Medium Industries, 2) Spatial Patterns, and 3) Industrial Impacts on Society. This type of research is included in the descriptive study. The population in this study are all large and medium industries in Padang Pariaman District. The sample of this research is all large and medium industries in the Padang Pariaman District taken by sampling technique that is total sampling where the number of samples is equal to the population. Data analysis techniques using the nearest neighbor analysis and descriptive analysis. The results of this study found that: 1) in Padang Pariaman District there were 57 large and medium industries spread across 9 Subdistricts of 17 Subdistricts. The distribution of large and medium industries is most found in Batang Anai Sub District with 31 industries. Based on industry classification, it is divided into 4 types, namely: industry based on the number of workers and capital, industry based on goods produced, industry based on type, and industry based on general activities carried out, 2) distribution patterns of large and medium industries in Padang Pariaman District more scattered cluster (cluster). For the pattern of distribution of large industries in Padang Pariaman District is more unevenly distributed (random pattern), whereas the tendency of the pattern of medium industry distribution in Padang Pariaman District is more spread in clusters, 3) Viewed from industrial growth in Padang Pariaman District from 2016 -2018 continues to increase so that the need for labor also increases. All of that greatly affects the welfare of society and the value of goods and services produced by the economic system in Padang Pariaman District.